Formation of GaN micro-crystals by the direct reaction of NH3 with a Ga-melt - Park, YJ; Son, MH; Kim, EK; Min, SK (KOREAN PHYSICAL SOC, 1998)
GaN micro-crystals were formed by using the direct reaction of NH3 with a Ga-melt. The bubbling technique was employed in an atmospheric NH3 ambient for about 20 hours at 850-1100 degrees C to achieve an effective reaction of the NH3 gas with the Ga-melt. A dark-gray-colored GaN material was formed. The GaN micro-crystals were synthesized without intentional nucleations and were refined by a chemical solution of HNO3 + HF. A kind of microcrystalline hexagonal structure was found from scanning electron microscope, X-ray diffraction, and Photoluminescence measurements. The systhesized GaN micro-crystals with a typical dimension of 0.5 - 3 mu m can be used as material for electronic devices or as a source material for growing thick GaN films by specific preparation techniques such as the sublimation method.
Keywords: MOLECULAR-BEAM EPITAXY; VAPOR-PHASE EPITAXY; GROWTH; SUBSTRATE; FILMS; LAYER